The Story Behind “London” (Loan Dito, Loan Doon): Exploring Teachers’ Expenditure Patterns and Debt Profile - Mary Cherry Lynn Mencias-Tabernilla (Universal Journal of Educational Research)
The study aims to determine the socio-demographic and debt profile of the public-school teachers in the Schools Division of Aklan, Philippines, their reasons on acquiring debt and perceived ways to avoid debts. This study utilized descriptive correlational research design utilizing a researcher-made instrument on socio-demographic profile, pattern of expenditures, debt profile covering the type of debts, total cost of debts, reasons for having debts and perceived ways to manage debts. The data gathered were tabulated and analyzed using the IBM Statistical Package for Social Sciences (SPSS) version 26. The take-home pay of the teachers was only more than half of their gross income. Most of the spouses of the married teachers were employed but many of them have relatively lower income. Their monthly family income was higher than the reported average family income for 2022 and their expenditures are also relatively higher than the average family expenditures in provinces for 2022. Almost one-half of the income of the teachers was used to pay their debts – both thru automatic payroll deduction and thru personal transactions. The bigger the household size, the higher the expenditure because there were more needs and there were many people consuming commodities. The higher the family income, the bigger the expenditure since lifestyle often adjusts with income. Young; married teachers; those occupying higher position and longer tenure have higher cumulative debts. Increase in family expenditure could cause increase in the number of debts as linked to the Theory of Reasoned Action and Theory of Planned Behavior. High regard for education, health, and safety triggered teachers to have debts, which can only be avoided thru better money and lifestyle management and having additional source of income.